The way we jam - KRU; EMI (Malaysia) (Selangor : EMI (Malaysia), 1998)
Contains four different versions of the single taken from the album The Way We Jam.
The Way We Jam (3:54) -- The Way We Jam (Swing to the mix) (4:00)-- The Way We Jam (John Boy's Jam) (5:15) -- The Way We Jam (Instrumental) (3:55).
Koleksi Khas Wiramanja.
Title from disc label.
Keywords: Rap (Music).; Popular music -- Malaysia